Pengaruh Disiplin Belajar, Status Gizi, Kebugaran Jasmani dan Pola Asuh Orang Tua terhadap Hasil Belajar Pendidikan Jasmani Olahraga dan Kesehatan (PJOK) Peserta Didik pada Masa New Normal di SMP Negeri 2 Airpura - Warda, Oyatra Utama; Damrah, Damrah; Pitnawati, Pitnawati (Ilmu Olahraga, 2021)
The main objective of this study was to examine the effect of learning discipline, nutritional status, physical fitness and parenting style on the learning outcomes of students' physical education, sports and health (PJOK) during the new normal period at SMP Negeri 2 Airpura. This research uses quantitative methods. The population taken in this study were students of class VII, VIII, and IX totaling 195 students. The sample was obtained through stratified random sampling so that the respondents in this study were taken 15% of the population in class VII, VIII, IX and totaled 29 respondents. The data analysis technique used is path analysis which is divided into 2 paths, namely sub-structure I and sub-structure II. Data were collected through a questionnaire with a Likert scale measurement. The findings show that there is a direct and significant influence of learning discipline on learning outcomes of PJOK of 0.367. The direct and significant effect of nutritional status on learning outcomes of PJOK is 0.241. The direct and significant effect of physical fitness on learning outcomes of PJOK is 0.220. The direct and significant effect of parenting style on learning outcomes of PJOK is 0.384. The indirect effect of learning discipline on learning outcomes through parenting is 0.468. The indirect effect of nutritional status on learning outcomes through parenting is 0.402. The indirect effect of physical fitness on learning outcomes through parenting is 0.319. The significant influence between learning discipline, nutritional status, physical fitness, and stimulant parenting of parents on learning outcomes of PJOK is 0.466. So it can be concluded that the dominant influence that is able to influence learning outcomes both directly and indirectly is learning discipline with a total of 21.90%.